Neonatal hypoxic-ischemic encephalopathy after acute carbon monoxide intoxication during pregnancy. A case report and brief review of the literature - Tuoni, Cristina; Nuzzi, Giulia; Scaramuzzo, Rosa Teresa; Fiori, Simona; Filippi, Luca (Frontiers in Pediatrics, 2023)
Carbon monoxide (CO) poisoning during pregnancy is a rare occurrence, associated with high maternal and fetal mortality rates. As CO can cross the placenta, leading to intrauterine hypoxia, CO intoxication can result in neurological sequelae and neurologic complications in fetuses who survive. We report a case of a preterm newborn acutely exposed to CO in-utero and delivered by emergent cesarean section at the 31st week of gestation due to the severe burns suffered by the mother following an indoor boiler explosion. As CO has serious adverse effects both on the mother and fetus, it is important to recognize and treat poisoning in a timely manner. Despite maternal blood CO levels, CO intoxication at critical stage of central nervous system development can lead to hypoxic-ischemic lesions, thus interdisciplinary care and follow up for these patients are mandatory.